THE INFLUENCE OF THE FARMER COURSE METHOD TOWARD THE PROCESS OF ADOPTING HYBRID CORN FARMERS IN NORTH OBA DISTRICT - Indrawati Ibrahim; Suwandi S Sangadji; Suhardi Suhardi (Jurnal Akrab Juara, 2019)
This study studied how to learn farming methods on the process of adopting hybrid corn farmers in the North Oba sub-district. This study uses a quantitative method of experiment with a survey, when the study was conducted in November until December 2018. The research location in Oba Utara District, Kota tidore Kepulauan was deliberately chosen. The analysis used in this study is Simple Linear Regression and the sample in this study were 50 Hybrid maize farmers in the North Oba sub-district, Tidore City, North Maluku Islands. Based on the results of the study, it can be concluded that the discussion using the farming method can discuss the significance of the process of adoption of hybrid corn farmers in the District of North Oba with a degree of influence of 51.8%.